The G protein‐coupled oestrogen receptor, GPER1, mediates direct anti‐inflammatory effects of oestrogens in human cholinergic neurones from the nucleus basalis of Meynert. (19th February 2020) - Sarchielli, Erica; Guarnieri, Giulia; Idrizaj, Eglantina; Squecco, Roberta; Mello, Tommaso; Comeglio, Paolo; Gallina, Pasquale; Maggi, Mario; Vannelli, Gabriella B.; Morelli, Annamaria
Abstract: It has been well established, particularly in animal models, that oestrogens exert neuroprotective effects in brain areas linked to cognitive processes. A key protective role could reside in the capacity of oestrogen to modulate the inflammatory response. However, the direct neuroprotective actions of oestrogens on neurones are complex and remain to be fully clarified. In the present study, we took advantage of a previously characterised primary culture of human cholinergic neurones (hfNBM) from the foetal nucleus basalis of Meynert, which is known to regulate hippocampal and neocortical learning and memory circuits, aiming to investigate the direct effects of oestrogens under inflammatory conditions. Exposure of cells to tumour necrosis factor (TNF)α (10 ng mL ‐1 ) determined the activation of an inflammatory response, as demonstrated by nuclear factor‐kappa B p65 nuclear translocation and cyclooxygenase‐2 mRNA expression. These effects were inhibited by treatment with either 17β‐oestradiol (E2 ) (10 nmol L ‐1 ) or G1 (100 nmol L ‐1 ), the selective agonist of the G protein‐coupled oestrogen receptor (GPER1). Interestingly, the GPER1 antagonist G15 abolished the effects of E2 in TNFα‐treated cells, whereas the ERα/ERβ inhibitor tamoxifen did not. Electrophysiological measurements in hfNBMs revealed a depolarising effect caused by E2 that was specifically blocked by tamoxifen and not by G15. Conversely, G1 specifically hyperpolarised the cell membrane and also increased both inward and outward currents elicited by a depolarising stimulus, suggesting a modulatory action on hfNBM excitability by GPER1 activation. Interestingly, pretreating cells with TNFα completely blocked the effects of G1 on membrane properties and also significantly reduced GPER1 mRNA expression. In addition, we found a peculiar subcellular localisation of GPER1 to focal adhesion sites that implicates new possible mechanisms of action of GPER1 in the neuronal perception of mechanical stimuli. The results obtained in the present study indicate a modulatory functional role of GPER1 with respect to mediating the oestrogen neuroprotective effect against inflammation in brain cholinergic neurones and, accordingly, may help to identify protective strategies for preventing cognitive impairments.